2006
DOI: 10.1096/fj.05-5007com
|View full text |Cite
|
Sign up to set email alerts
|

Activation of cerebral peroxisome proliferator‐activated receptors gamma promotes neuroprotection by attenuation of neuronal cyclooxygenase‐2 overexpression after focal cerebral ischemia in rats

Abstract: Up-regulation of cyclooxygenase (COX)-2 exacerbates neuronal injury after cerebral ischemia and contributes to neuronal cell death. The present study clarifies the function of cerebral peroxisome-proliferator-activated receptor(s) gamma (PPARgamma) in the expression of COX-2 in neurons of the rat brain after middle cerebral artery occlusion (MCAO) with reperfusion by immunohistochemistry, Western blot, and immunofluorescence staining. In peri-infarct cortical areas the PPARgamma was located in both microglia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
155
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(172 citation statements)
references
References 59 publications
14
155
0
2
Order By: Relevance
“…These findings strongly suggest that the upregulation of 5-LO induced by rosiglitazone is beneficial and mediates the neuroprotective effect of rosiglitazone after MCAO. Anti-inflammatory mechanisms have been demonstrated to mediate the neuroprotective effects of PPAR␥ agonists (Pereira et al, 2005(Pereira et al, , 2006Sundararajan et al, 2005;Zhao et al, 2005;Collino et al, 2006;Luo et al, 2006;Zhao Y et al, 2006;Tureyen et al, 2007). Our present data confirm this mechanism of rosiglitazone, as shown by the inhibition of the expression of inflammatory genes with a deleterious role in cerebral ischemia, namely, COX-2, iNOS, MMP9 and TNF-␣.…”
Section: Discussionsupporting
confidence: 88%
“…These findings strongly suggest that the upregulation of 5-LO induced by rosiglitazone is beneficial and mediates the neuroprotective effect of rosiglitazone after MCAO. Anti-inflammatory mechanisms have been demonstrated to mediate the neuroprotective effects of PPAR␥ agonists (Pereira et al, 2005(Pereira et al, , 2006Sundararajan et al, 2005;Zhao et al, 2005;Collino et al, 2006;Luo et al, 2006;Zhao Y et al, 2006;Tureyen et al, 2007). Our present data confirm this mechanism of rosiglitazone, as shown by the inhibition of the expression of inflammatory genes with a deleterious role in cerebral ischemia, namely, COX-2, iNOS, MMP9 and TNF-␣.…”
Section: Discussionsupporting
confidence: 88%
“…Troglitazone treatment reduced IL-1b mRNA in rat brain after 24 h of reperfusion in the MCAO model (Sundararajan et al, 2005). Pioglitazone has been shown to reduce TNFa in the rat MCAO model after 24 h of recovery (Zhao et al, 2006). It is interesting that, despite their extensive use in the treatment of type II diabetes and several reviews indicating their efficacy in improving stroke outcome in diabetic patients (Culman et al, 2007;Kapadia et al, 2008), only one study examined the effects of PPAR-g agonists on stroke recovery in an animal model of diabetes (Tureyen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported a TZD-mediated neuroprotection after middle cerebral artery occlusion (MCAO) in normal rats (Pereira et al, 2006;Shimazu et al, 2005;Sundararajan et al, 2005;Zhao et al, 2006) and mice (Luo et al, 2006;Tureyen et al, 2007). These reports suggest that PPAR-g activation in brain suppresses microglial activation and macrophage accumulation, and reduces overexpression of neurodegenerative target genes such as inducible nitric oxide synthase and cyclooxygenase-2.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that both rosiglitazone and pioglitazone are neuroprotective in animal models of acute focal ischemia. 3 Studies have also shown that neuroprotection by TZDs following ischemia may involve: (a) a reduction in the inflammatory response, such as by upregulation of nuclear factor-kB, intercellular adhesion molecule-1, or cyclooxygenase; [16][17][18][19] (b) activation of an anti-inflammatory mediator, such as synthesis of lipoxin A 4 by 5-lipoxygenase expression; 20 (c) activation of superoxide dismutase; 21,22 or (d) prevention of harmful neuronal responses to ischemic insult, such as enhanced 14-3-3e expression. 23 There is significant evidence from these studies that PPARg activation is involved in neuroprotection.…”
Section: Discussionmentioning
confidence: 99%